Multicultural Education and Its Implementation in the Field of Education - ManArfa, Arman; Lasaiba, Djamila (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
Multicultural education in schools is crucial for creating an inclusive, tolerant, and harmonious society in Indonesia. In a multicultural learning environment, students can gain a broader understanding of the world, learn to communicate with people from different cultures and build harmonious relationships. The implementation of multicultural education in schools can also help address discrimination and intolerance that still exist in society and better prepare students to face the challenges of an increasingly complex world. To achieve the implementation of multicultural education in schools steps such as raising awareness and understanding of the importance of multicultural education, creating spaces for dialogue and communication with students, parents, and the community, and providing adequate support and resources are necessary. Through the implementation of multicultural education in schools, students can build mutual understanding, tolerance, and cooperation with people from different cultures, thereby contributing to a more inclusive, tolerant, and harmonious society.